Prolonged small-intestinal transit time in cystic fibrosis. Issue 6398 (8th October 1983) - Bali, A; Stableforth, D E; Asquith, P
Abstract : A lactulose hydrogen breath test was performed on 10 patients with cystic fibrosis and 15 control subjects matched for age and sex. All normal subjects had a fasting breath hydrogen concentration of less than 20 ppm. In contrast, seven of the patients with cystic fibrosis had high concentrations (25-170 ppm), which fell to 20 ppm or below on prolonged fasting (14-23 hours). Two patients showed no rise in breath hydrogen concentrations after lactulose, and in one patient the breath hydrogen concentration rose at 15 minutes, suggesting bacterial colonisation of the small bowel. Seven of the patients had prolonged small-bowel transit times (160-390 minutes) compared with those in the control group (50-150 minutes).